Vedovamazzei : Caveau. - Orlofsky, Sam; Scotini, Marco; Palazzo delle Papesse Centro Arte Contemporanea, Siena (Siena : Palazzo delle Papesse, 2002)
Caveau is an exposition cycle articulated within one of the most singular spaces of the Contemporary Art Center : the armored room constructed in 1952 by the Bank of Italy, which was then located in Palazzo delle Papesse. The room, still intact and with its original furnishings, from iron cabinets to the amored door, lends itself very well to becoming a sort of project room, entrusted in turn to artists who are able to come to terms, with such a strongly characterized and difficult to interpret place. Here, the work of art must necessarily find other channels of interaction, or it runs the risk of being annulled. The caveau, therefore, is never configured as Container, but aspires to become one of its constituting parts.
Vedovamazzei : Simeone Crispino & Stella Scala.
bilbiog. p. 56-60
biog. , ind. tent., gr. tent. p. 48-53
Engels
Italiaans
Vedovamazzei : Caveau, Palazzo delle Papesse Centro Arte Contemporanea Siena, 7 dicembre2002 - 23 febbraio 2003
Keywords: Vedovamazzei